Effects of knife angles and cutting speeds on pulverization of sweet potato vines - Kakahy, Amer Najat Najmaldeen; Ahmad, Desa; Hamid, Md. Akhir; Sulaiman, Shamsuddin; Aris, Ishak (School of Social Sciences, Universiti Sains Malaysia, 2012)
A study was conducted to investigate the effects of three different knife angles (30, 40 and 50°) and three different speeds (1830, 2066 and 2440 rpm) of a Mower on sweet potato vine slashing (pulverizing) The results showed that all the treatments were significant at 99% significance level on the percentage of pulverized vines. The best results were for the first knife angle (30°) with the lowest vine pulverized of 57.59%. The third speed (2440 rpm) had the best vine pulverized percentage of 54.00%. The best performance for overlapping effect between knife angle and speed of mower was achieved by the 30° knife angle at 2440 rpm with average vine pulverized percentage of 38.73%.